Implementation of Quality Management in Improving Academic Services - Riduan; Mardianto; Rifa'i, Muhammad (STAI Miftahul Ula Nganjuk, 2024)
This study aims to analyze and evaluate (1) the quality planning for improving academic services at STAI-JM Tanjung Pura, (2) the quality control measures implemented to enhance student academic services at STAI-JM Tanjung Pura, and (3) the strategies for quality improvement in student academic services at STAI-JM Tanjung Pura. This research adopts a qualitative approach, utilizing data collection methods such as observation, interviews, and documentation. The collected data were analyzed using descriptive qualitative analysis. The findings of this study are as follows: (1) The planning for academic service quality involves the university's strategic plan (RENSTRA), which outlines goals for academic services, including E-Journals, E-Letters, academic calendars, student guidelines, and student activities. (2) Quality control in academic services is achieved through strategic planning that facilitates the delivery of both academic and non-academic services to students. (3) STAI-JM Tanjung Pura enhances the quality of its academic services by strengthening collaborations with relevant stakeholders, including government agencies, the Ministry of Religious Affairs, and educational institutions both domestically and internationally. These partnerships aim to provide opportunities for students to expand their knowledge, such as through training programs and community service (KKN).